Design of Optimal Filter for Analog Signal - Roman Fedoryshyn; Sviatoslav Klos; Volodymyr Savytskyi; Yevhen Pistun; Miroslaw Woloszyn (Energy Engineering and Control Systems)
The technique for designing the optimal value of the filter time constant for analog signal is presented in the paper. This technique is based on the objective function which takes into account the quality index of the filtration process and the dynamic error of the filtered signal. The experimental study of the transient processes in a thermal plant was carried out in order to analyze the influence of the filter parameters on the quality of the filtration process. The optimal value of the filter time constant was designed on the basis of the developed technique for the obtained experimental data. The experimental transient process was compared to the filtered one which was obtained with application of a filter with an optimal time constant. Application of the developed technique for designing the optimal time constant in the automated measurement and control systems will ensure high quality of the filtration process and small dynamic error of the filtered signal.